The Problem of Multidrug Resistance Bacterial Strains in Daily Clinical Practice in Dealing with Typhoid Fever in Mid-Euphrates Region of Iraq: A Cross Sectional Study - Huda Jabbar Dibby1, Radhi Farhod Shlash2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: in our community, typhoid fever is common infectious disease based on daily clinical practice and the emergence of multidrug resistant strains a evidenced by worldwide reports and our daily clinical observation necessitate optimizing antibiotic approach to treat such common infectious disease.Aim of the study: we aimed in this study to highlight the problem of multi-drug resistance in daily clinical practice when treating typhoid fever.Patients and methods: The present cross sectional study included 95 cases with clinical and laboratory evidences of typhoid fever. Venous blood sample was obtained from each patient and sent to the lab for purpose of culture and sensitivity. The study was carried out at the department of Medicine / Al-Diwaniyah teaching hospital, Al-Diwaniyah province, Mid-Euphrates region of Iraq. The study started on January 2018 and extended through October 2018.Results: Regarding amoxicillin, azithromycin and cefotaxime, isolates obtained from 60 patients (63.2 %) were resistant whereas isolates from 35 patients were sensitive. Ciprofoxacin and ceftriaxone were totally ineffective since resistance was recorded in all enrolled isolates (100.0 %). On the other hand, chloramphenicol, trimethoprim-sulphamethoxazole and imipenem produced the best results since all isolates were sensitive to these antibiotics. The resistant strains of Salmonella enterica serotype typhi were more associated with urban areas than with rural regions, 75 % versus 58.2 %; however, the difference did not reach statistical significance (P > 0.05).Conclusion: antibiotic approach to typhoid fever is a dynamic rather than a static phenomenon that needs revision regularly and that drug individualization according to culture and sensitivity rule should be adopted by all health workers and institutes when dealing with outbreaks of Salmonella enterica serotype typhi.